Acoustic wave motions stabilized by boundary memory damping II. Polynomial stability. (November 2018) - Jiao, Zhe; Xu, Yong
Abstract: A linear wave equation with acoustic boundary conditions (ABC) on a portion of the boundary and Dirichlet conditions on the rest of the boundary is considered. The ABC contain a memory damping with respect to the normal displacement of the boundary point. In this paper, we establish polynomial energy decay rates for the wave equation by using resolvent estimates.